THE RELIGIOUS TOLERANCE IN MALAYSIA - Turdieva Dilafruz Makhmudjanovna (Modern American Journals, 2025)
Religious tolerance in Malaysia is acknowledged by many and disputed by few. One of the many factors contributed to Malaysian economic development and growth is the existence and maintenance of religious tolerance and harmony among Malaysian multi-religious and multi-racial citizens. This article aims at explaining the reasons or factors for the existence of religious tolerance and harmony in Malaysia although its citizens are Muslims, Christians, Buddhists, Hindus and other religious adherents. The highest leaders of Malaysia namely the Prime Minister and the King are Muslims. Malaysians are able to maintain the religious tolerance and harmony because there are reasons or factors supporting the Muslims, Hindus, Buddhists and Christians in Malaysia; these factors are the religious teachings and approaches encouraging their adherents to live in a moderate, tolerant and harmonious situation, the constitution of Malaysia which guarantees the rights of each Malaysian citizen regardless of their religious adherence and ethnicity, the Malaysian legal system provided for all Malaysians and Islamic legal system for Muslims only in relation to their personal laws, marriages and inheritances, and the Malaysian government declared policies and orientations promoting religious tolerance and harmony such as Islam Hadhari and One Malaysia.
Keywords: Malaysia, Religious tolerance, Islam Hadhari, One Malaysia.